Experimental investigation on mechanical properties of conventional concrete using pineapple leaf fiber and coconut fiber as an admixture - Gutierrez, Rusell M. (2023)
Most of the construction industry had been using admixtures to increase the various properties of concrete. These added materials are used as a reinforcing material in place of steel in concrete. With this, pineapple leaf fibre (PALF) and coconut fiber are mixed as an alternate non-degradable matter admixture which is not in demand of abundance and cheaper in the cost. As fibers in concrete were mixed, an experimental test was conducted to measure the strength of concrete containing PALF and Coir given the standard ratio of water-cement. The various dosage of PALF and Coir are at 0.1% each, 0.75% each, and 3% Coir only based on the fiber-cement ratio. Each concrete mixture formula was cured for 28 days as their compressive and flexural strength test were conducted. Other tests were used to analyzed the properties of fiber concrete. Using the universal testing machine (UTM) to test the compressive and flexural strength, results were analyzed on which ratio had the best compressive and flexural strength. The newly built material was applied on the design project named Coña. It is a condominium complex that is designed as tropical paradise with its unrivaled resort-like amenities, large units, generous open spaces, and luxurious greeneries. The condominium building serves as a symbol of how housing is still evolving and the need for a harmonious balance between solitude and social interaction. The developed material was used on the project to separate areas for privacy and other purpose of the room. It was used as decorative material and accent wall to highlight the use of material. It creates another purpose to improve the function of an area. The application of the material is a point of interest of our project since its new and could be more developed. Thus, this will help the construction industry on what type of concrete will be used on other projects such as housing, commercial buildings, and many more. It will also help the construction industry of having less environmental impact since it is using agricultural waste. The agricultural industry will also benefit fro the building material since it will be using agricultural waste turn into a new product. The research underlines material's potential as a ground breaking building material that addresses the pressing environmental challenges faced by the construction industry. With its sustainable attributes, exceptional performance, and design flexibility, the newly developed material offers a promising pathway towards constructing energy-efficient and eco-friendly buildings, paving the way for a greener and more sustainable future for the architectural industry.